2015
DOI: 10.7326/m14-0611
|View full text |Cite
|
Sign up to set email alerts
|

Single-Component Versus Multicomponent Dietary Goals for the Metabolic Syndrome

Abstract: Background Few studies have compared diets to determine if a program focused upon one dietary change results in collateral effects on other untargeted healthy diet components. Objective To evaluate a diet focused on increased fiber consumption versus the multi-component American Heart Association (AHA) dietary guidelines. Design Randomized controlled trial; June 2009 to January 2014. Trial registration: NCT00911885 Setting Worcester, Massachusetts. Patients 240 adults with metabolic syndrome. Interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…31 A recent randomized controlled trial reported that increasing fiber intake may lead to other healthy dietary changes and facilitate weight loss. 32 Greater whole grain consumption is also associated with a lower risk of adverse chronic conditions, including type 2 diabetes, cardiovascular diseases, and weight gain. 5 Thus, promoting the consumption of greens and beans and whole grains could improve overall diet quality among women with young children.…”
Section: Discussionmentioning
confidence: 99%
“…31 A recent randomized controlled trial reported that increasing fiber intake may lead to other healthy dietary changes and facilitate weight loss. 32 Greater whole grain consumption is also associated with a lower risk of adverse chronic conditions, including type 2 diabetes, cardiovascular diseases, and weight gain. 5 Thus, promoting the consumption of greens and beans and whole grains could improve overall diet quality among women with young children.…”
Section: Discussionmentioning
confidence: 99%
“…The RCT compared two 14 sessions dietary counseling interventions which differed only in the content of the dietary recommendations provided (Ma et al, 2015). Results indicated significant weight loss within each condition, and no significant differences in weight loss between conditions (Ma et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Ma et al 1 also were concerned about how much information should be provided to a patient so that he or she does not become overwhelmed with the material; they viewed this issue as a challenge yet to be answered. They concluded the Discussion section by expressing optimism over the associated improvements in blood pressure, dietary quality, and insulin resistance that occurred during the year in the recipients of the high‐fiber diet.…”
mentioning
confidence: 99%